(3GdeYQH ef GdcdGe GdCYLeis - (3ehghH Hf CMeO Hf eMeO Hf GdNVQ Hf GdMSf, CHh GdefUhQ GHf GdLhGdjbj,J (B540 (3g` s
(3ChdgG (B:s
(3gPG cJGH fPcQ ajg eG JcedJ Hg GdYQH ef GdcdGe GdCYLei hfWb Hg GdbQBf GdeLjO hgj Cf jMJQS GdeTJb adG jLYd TjFkG ef dZI GdYQH dTF ef dZI GdYLe s
(3BNQgG (B:s
(3bGd CHh MGJe abdJ (B: (3cja Jbhd GdGKfjf hGdLejY hGdeDfK , ade jOQ bGd CHh MGJe (B: (3CXf CUdg HGdSQjGfjI (B: (3jGgGjG TQGgjG Je GdcJGH s
(3HBNQgG bQGAI JeJ SfI (B560 (3hHChdgG Cfg fbd efgG fSNI SfI (B562 (3g`s
(3Ydi MQha GdeYLes
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B53s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1739s
Keywords: (3GddZIs